Magnetic particles-based chemiluminescence immunoassay for progesterone determination - Phakthong W. (2017)
© 2017, Chiang Mai University. All rights reserved. A magnetic particles-based chemiluminescence immunoassay was investigated for progesterone detection by using luminometer. In this work, progesterone was determined based on the competitive binding between progesterone in the sample and progesterone-horseradish peroxidase (HRP) conjugate for a constant amount of rabbit anti-progesterone. Initially, anti-rabbit IgG coated magnetic particles conjugated with primary progesterone antibody were bound to progesterone in the samples. Then, the amount of progesterone was quantified by reacting with the residual unoccupied antibody sites with HRP-progesterone, followed by HRP substrate (luminol, H 2 O 2 , and p-iodophenol (PIP)) and finally detection of the generated chemiluminescence by a luminometer. The intensity of the emitting light was proportional to the amount of enzyme present (HRP-progesterone) and was inversely related to the amount of unlabeled progesterone in the sample. The optimum conditions for determination of progesterone were obtained at 0.15 μg L -1 magnetic particles, 5.0x10-4 mol L -1 luminol, 5.0 × 10 -3 mol L -1 H 2 O 2 , 1.0 × 10 -3 mol L -1 PIP, and phosphate buffer saline buffer pH 9. The optimal dilutions of both anti-progesterone antibody and HRP-progesterone conjugate were 1:1000. The linear relationship between chemiluminescence intensity (RLU) and various concentrations of progesterone was over the concentration range of 0.5-50.0 μg L -1 . This proposed method had been successfully applied to the evaluation of progesterone in human sera.